Terminalia Chebula provides protection against dual modes of necroptotic and apoptotic cell death upon death receptor ligation - Lee, Yoonjung (Sci Rep, 2016)
Death receptor (DR) ligation elicits two different modes of cell death (necroptosis and apoptosis) depending on the cellular context. By screening a plant extract library from cells undergoing necroptosis or apoptosis, we identified a water extract of Terminalia chebula (WETC) as a novel and potent dual inhibitor of DR-mediated cell death. Investigation of the underlying mechanisms of its anti-necroptotic and anti-apoptotic action revealed that WETC or its constituents (e.g., gallic acid) protected against tumor necrosis factor-induced necroptosis via the suppression of TNF-induced ROS without affecting the upstream signaling events. Surprisingly, WETC also provided protection against DR-mediated apoptosis by inhibition of the caspase cascade. Furthermore, it activated the autophagy pathway via suppression of mTOR. Of the WETC constituents, punicalagin and geraniin appeared to possess the most potent anti-apoptotic and autophagy activation effect. Importantly, blockage of autophagy with pharmacological inhibitors or genetic silencing of Atg5 selectively abolished the anti-apoptotic function of WETC. These results suggest that WETC protects against dual modes of cell death upon DR ligation. Therefore, WETC might serve as a potential treatment for diseases characterized by aberrantly sensitized apoptotic or non-apoptotic signaling cascades.